Keandalan Jaringan Distribusi Di Pulau Panjang Dengan Pembangkit Listrik Tenaga Diesel - Samsurizal Samsurizal; Arova Putra (Sekolah Tinggi Teknik - PLN, 2023)
By examining the issue of the electrical power distribution system's dependability, particularly on the outer islands, in this case Pulau Panjang, it can be seen that the usage of electrical energy in Indonesia is still predominantly controlled by steam power plants. It is discovered that the Diesel Power Plant is this location's primary source of electrical energy. Since 2019, the use of PLTD has been running continuously here, with four primary engines operating efficiently. However, each day, only two machines run alternately for 12 hours, raising a reliability concern that has to be looked into. The SAIDI and SAIFI values obtained using these approaches are extremely high (403,645 for SAIDI and 16 for SAIFI), Then, it was claimed that an index comparison based on SPLN 68-2: 1986, IEEE, and WCS as of January 2022 to June 2022 was erroneous. Thus, the installation of PLTS in the Long Island region is required as a substitute for electrical energy. In order to achieve optimal performance, the diesel working time limit is decreased using the PLTS technology